Biomechanical evaluation of movement in sport and exercise the British Association of Sport and Exercise Sciences guide - Payton, Carl; Burden, Adrian (Adrian M.); British Association of Sport and Exercise Sciences (London New York Routledge, Taylor & Francis Group, 2018)
Now in a fully updated and revised edition, this is still the only up-to-date, practical guide to the use of technology in sport and exercise biomechanics. it includes detailed explanations of the key theory underlying biomechanics testing and measurement, along with advice on choosing equipment and using it effectively. The second edition includes two completely new chapters on qualitative movement analysis and the assessment of movement coordination, and covers every key functional area in the biomechanics curriculum, including: motion analysis of force using video and on-line systems; measurement of force and pressure; measurement of torque and power using isokinetic dynamometry; electromyography; computational simulation and modelling of human movement; research methodologies; data processing
1. Introduction -- 2. Qualitative biomechanical analysis of technique -- 3. Assessing movement coordination -- 4. Motion analysis using video -- 5. Motion analysis using on-line systems -- 6. Measurement of external forces -- 7. Surface electromyography -- 8. Isokinetic dynamometry -- 9. Data processing and error estimation -- 10. Research methods: sample size and variability effects on statistical power -- 11. Computer simulation modelling in sport
"The British Association of Sport and Exercise Sciences"--Title page
Includes bibliographical references and index
Keywords: Human mechanics; Exercise -- Physiological aspects; Sports -- Physiological aspects